Tidal correlation of deep tectonic tremors increases during long-term slow slip events in the Bungo Channel, southwest Japan - Fuyuki Hirose; Akio Kobayashi (Earth, Planets and Space)
Abstract In the Bungo Channel along the Nankai Trough, southwest Japan, long-term slow slip events (LSSEs) of about $${M}_{\text{w}}$$ M w 6–7 and lasting 6–12 months occur at several-year intervals at the base of the seismogenic zone. In sync with these LSSEs, deep tectonic tremors are activated at the base of the LSSE zone. The tidal response of tectonic tremors during short-term slow slip events lasting several days has been extensively investigated, but variations of the tidal correlation of tectonic tremors over periods on the order of years remain poorly understood. Here, we investigated long-term temporal changes in the correlation between deep tectonic tremors and tides in the Bungo Channel. We found that tectonic tremors along the base of the LSSE region (region Ba) are strongly correlated with tidal shear stress and/or Coulomb failure stress under a very small apparent friction coefficient, and that these tremors are more likely to occur when the tidal stress acting in the direction promoting fault slip is large. We also found that tidal sensitivity is relatively high during LSSE periods and low during other periods. Because the LSSE region largely includes region Ba, fault coupling in region Ba during LSSE periods is undoubtedly smaller than during other periods. As a result of this low friction state, even tidal stresses much smaller than the lithostatic stress can affect the generation of deep tectonic tremor, and tidal sensitivity during LSSE periods seems to be higher than during other periods. Graphical abstract